Guidelines for low cost terminal (LCT) development : Case study of Kuala Lumpur International Airport Low Cost Terminal, Malaysia - Sabar, Rohafiz; Fewing, Rodney (2010)
The purpose of the Paper is to suggest guidelines for the provision of passenger, facilities Low Cost Terminals (LCTs) after reviewing a selection of LCT models at airports in the Asia Pacific, European and United States regions, and supported by an in-depth survey of passenger, airline management and airport management preferences related to operations at the Low Cost Terminal, Kuala Lumpur International Airport. The decision by airport management for the provision of specific terminal facilities (TFs) may be dependent on budget restrictions, cost of investment, land availability and the preferences of the major customers, that is, in the case of LCTs, the low-cost carriers (LCCs). Consequently, most (but not all) LCT designs are based on the concept of a basic terminal layout with limited terminal facilities in order to reduce both construction and operating costs, a shorter construction time, acceptable service standards and minimum aircraft turnaround time. However, there are contradictions. For example, passenger expectations of terminal facilities do not always coincide with those of airline and airport management. Furthermore, a consequent low level of aeronautical revenue drives the requirement to maximise commercial revenues. The paper will conclude by suggesting guidelines for LCT development that will seek to optimise the relative aspirations of all parties concerned.